(untitled) (Journal of Science and Technology, 2016)
Thirty regular school children with functional articulation and phonological disorders, aged 7; 0 to 17; 11, were involved in the study. They were screened for speech defects from selected schools in the Kumasi metropolis. Effects of maturation were controlled for by the inclusion of only children of seven years and above who had reached their limit for spontaneous acquisition of phonemes by adult standards. The study investigated the children’s age versus their school grades, their class performance, the emergence of their speech and language milestones, differences in their speech mechanisms, the intelligibility of their speech and the treatment outcome. The result indicated a sex ratio of 1:6.5 females to males. Only 10% of the children were in their normal school grade level while 90% were in various grade levels below the normal. Fifty percent were rated as below average, 46.7% as average and 3.3% as below average. Considering the time for speech and language acquisition, 63.3% were considered normal while the rest were considered delayed. While 50% had “normal” tongue, 16.7% had ankyloglossia, 30% had limited tongue movement and 3.3% had macroglossia. However these tongue differences were considered insignificant due to the adequacy of the tongue structure in its performance. Twenty percent sounded hypernasal but correction of their misarticulations solved their problems. Baseline intelligibility rates were: moderate-30%; moderate- severe 30%, and severe-40%. Therapy gains were 90-100% for 73.3% of the children; 70-80% for 20% of them and 50-60% for 6.7% of the rest. By these gains, the children had improved skills for effective communication, a great sense of pride and confidence and a fully active social life.